The Calibration Test Of Hybrid Landfill Gas -Photovoltaic-Genset Model In Bontang, East Borneo - Salama Manjang; Sitti Hamnah Ahsan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The study is aimed to determine the measurement of sensor tool made in Model Real Time Hybrid LFG-PV-Genset by finding the correction factor produced at TPA Bontang City, East Borneo. The research was conducted by using ampere clammeter, variable voltage regulator, thermometer, odalog7000 series.  The calculation results  show that the calibration test of Model Real Time Hybrid LFG-PV-Genset from MQ4 sensor data that has been designed capable of having errors of 1,91% and the LM35 temperature sensor is capable of monitoring tempertures of 30°C to 120°C and has an error value of 0,519°C. ZMPT 101B voltage sensor has a linear output change to input changes and has an average error of 1.499V. While the current sensor SCT 013 has an aerage error value of 0,0022A CO2.